The nature and relevance of risk and protective factors for violence among Hispanic children and adolescents: Results from the Boricua Youth Study. (June 2016) - Jennings, Wesley G.; Gonzalez, Jennifer Reingle; Piquero, Alex R.; Bird, Hector; Canino, Glorisa; Maldonado-Molina, Mildred
Abstract: Purpose: While there exists much literature devoted to identifying risk and protective factors for violence, Hispanic research in this area is still in its infancy. Methods: The current study provides the most comprehensive study to date on this topic by utilizing data from 1138 Puerto Rican youth who were participants in the Bronx, NY sample of the Boricua Youth Study (BYS). Results: Relying on a myriad of descriptive and multivariate analyses examining the nature and role of 8 risk factors and 9 protective factors distributed across 6 risk/protective factor domains, the results suggest that cumulative risk factors significantly increase a Hispanic youth's odds of violence participation whereas cumulative protective factors offset this risk to some degree by decreasing the odds of violence participation. These results largely hold across different developmental age groups (ages 5–9 and ages 10–13) and over time (Waves 1, 2, and 3). Conclusions: These findings have theoretical and policy implications for violence prevention among Hispanic youth. Highlights: Cumulative risk factors increase a Hispanic youth's odds of violence. Cumulative protective factors decrease a Hispanic youth's odds of violence. Results largely hold across different developmental age groups. Results largely hold across different time periods.